This is My Country (?) Exploring Denial in Relation to the Negative Aspects of Nationalism in Indonesia. - Edward Salim; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
Nationalism is a central part of Indonesian ideology, but few Indonesians recognise or acknowledge its more negative elements out of denial. As such, the nation rarely addresses the numerous human right violations committed in the past for the sake of upholding this ideology. In response to this issue, I wrote this novel to show the detrimental effects of denial have on people, as well as the way to cope with it. This creative work takes on the perspective of a soldier in the New Order era, who in the effort to find his missing brother, encounters the harsh reality in Buru island that forces him to reconsider his naïve understanding of nationalism.Keywords: Denial, Nationalism, Nation, Indonesia, Buru, Historical Fiction, History, Novel